A polarized scanning nephelometer for measurement of light scattering of an ensemble-averaged matrix of aerosol particles. (March 2021) - Hu, Qiang; Qiu, Zhenwei; Hong, Jin; Chen, Dihu
Highlights: A new instrument for measuring the complete scattering matrix of aerosol particles. Measurements for artificial aerosols are in agreement with theoretical calculations. The average residual errors for DEHS droplets were within 0.025 (normalized by F 11 ). Abstract: A new instrument, the Polarized Scanning Nephelometer (PSN), has been developed for measuring the complete scattering matrix of aerosol particles as a function of the scattering angle. The instrument measures directly the ensemble-averaged scattering matrix elements of the aerosol particles and can deduce all scattering matrix elements for scattering angles in the range 3.5° to 170° at two different wavelengths (445 nm, 633 nm). The PSN instrument features a number of different optical components including beamsplitters, polarizers, and quarter-wave plates. By using different combinations of orientation angles for the optical components, all the scattering matrix elements are obtained as a function of the scattering angles. Nitrogen gas was used to give a measure of the stray light suppression level of the instrument. Instrument performance in terms of the accuracy of the scattering matrices was verified quantitatively using homogeneous polydisperse spherical particles. For instance, in studies comparing the PSN measurements with Mie calculations, the average absolute relative errors of the scattering matrix elements for diethylhexyl sebacate (DEHS) droplets were within 0.02 and 0.025 at 445 nm and 633 nm, respectively.